Probing charge trapping and joule heating in graphene field-effect transistors by transient pulsing. (24th July 2017) - Ramamoorthy, H; Somphonsane, R; Radice, J; He, G; Nathawat, J; Kwan, C-P; Zhao, M; Bird, J P
Abstract: We use pulsed electrical studies to investigate the various processes that limit the current carrying capacity of graphene high frequency transistors. By investigating the transient response of these devices over a time scale that spans some twelve orders of magnitude, we identify the presence of four distinct processes that degrade the current: (1) charge injection into deep traps within the interior of the oxide; (2) Joule heating of the transistor substrate by hot carriers in the graphene channel; (3) equilibration of interfacial-state filling in response to voltage transients, and; (4) leakage of captured charge from the deep traps, once the pulsed voltage is removed. The time scale associated with these processes ranges from nanoseconds to hours, with process (1) being the fastest and process (4) the slowest. By pulsing the transistors on time intervals as short as a few nanoseconds, we therefore demonstrate how it is possible to obtain output characteristics from them that are essentially free from the influence of these different mechanisms. Under such conditions, the hot-carrier drift velocity is shown to saturate at the large values expected for intrinsic graphene. Beyond graphene, this approach of pulsed characterization of transistor performance should be broadly applicable to studies of other two-dimensional semiconductors, including transition-metal dichalcogenides, black phosphorous, silicene, and topological insulators.